Notes on the foundation of the Federal Theological Seminary of Southern Africa (Fedsem) - Duncan, Graham (Verbum et ecclesia, 2006)
The Federal Theological Seminary of Southern Africa was established in a changing and fluid situation in 1960s South Africa both politically and ecclesiastically. Its foundation can be attributed to the influence of these national and church influences. Politically, the changing context in the educational world in particular and ecclesiastically, a growing tendency towards ecumenism both nationally and internationally contributed to the need for an independent institution which would train ministers for the mainline churches in a deteriorating political context. In addition, there was a strong view that the influence of the Holy Spirit was operative in the political context which ‘forced the church to be the church’.